Research on using beta-lactam antibiotics in outpatients under 12 years old at Thoi Hoa General Clinic, Ben Cat City, Binh Duong Province in the first six months of 2024 - Duong , Thị Xuân; Le , Văn Út; Nguyen , Thị Ngọc Phượng; Trieu , Thị Ngọc Oanh; Tran , Huyền Trân (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Nowaday, antibiotic resistance has developed all over the world, particularly in developing nations such as Vietnam. Many bacterial strains are resistant to a wide range of antibiotics, including newer generations. The study aimed to research the use of beta lactam antibiotics at Thoi Hoa General Clinic, Ben Cat City, Binh Duong Province in the first six months of 2024, using a cross-sectional descriptive retrospective method on 400 outpatient prescriptions for beta lactam antibiotics treated at Thoi Hoa General Clinic departments in the first six months of 2024.The results showed that the rate of antibiotic use in outpatient treatment was 48.75%, with male cases accounting for the highest rate (55.7%). Patients treated with antibiotics were mainly in the age group over 60 years old (45.5%), the respiratory disease group had the highest rate of antibiotic use (43.6%), and the Otolaryngology department had the highest rate of antibiotic use (88.9%). Cephalosporin antibiotics were the most commonly prescribed (74.9%), and no prescriptions for three antibiotics were written together. Antibiotics were used appropriately 98% of the time, with only 2.0% of prescriptions lasting 10 days or longer.